(untitled) (American Journal of Islam and Society, 1997)
The focus of this book is on "the gradual transformation of American Muslims’ perceptions and self-identification, coaxed by the ways American civil law has penetrated and come to dominate their daily lives" (p. vii). Hence, the book attempts to show the link between law and society by using Muslims in the United States as a case study. It is of interest to sociologists, legal historians, political scientists, and scholars of religion and touches on the themes of civil rights, freedom of religion, social change, the status of minorities, and assimilation. Moore shows how Muslims in the United States have been affected by American immigration law (chapters 2 and 3), religious liberty laws affecting Muslims in prison (chapter 4), hate crime legislation affecting mosques (chapter 5), and zoning laws that affect mosques (chapter 6). The sources Moore uses are historical: court records, interviews, magazine articles, and newspaper stories. She points out that there has been a great transformation in the American legal system’s attitude toward Islam. In 1811, the New York Supreme Court ruled (in People vs. Ruggles) that the "religion of Mohammed" is an impostor religion, a superstition, and is equally false and unknown (p. x). ln 1962, on the other hand, the District of Columbia U.S. District Court ruled (in Fulwood vs. Clemmer) that Muslims believe in Allah as a supreme being and as the one true god. It follows, therefore, that the Muslim faith is a religion p. 82). Have American legal institutions been responsive to the Muslim community? Has the American legal setting transformed the Muslim community? The answer to the first question, according to Moore, is that in the 1800s, "No"; but gradually the courts have become more responsive and continue to be more responsive as time passes and as Muslims become more politically active. The answer to the second question is "Yes." How has the American legal setting transformed the Muslim community? It has limited the numbers of Muslims in the United States (through immigration restrictions). It has increasingly allowed Muslims in prison to pray jum’ah, wear kufis on their heads, eat nonpork foods, and obtain copies of the Qur’an. It has protected Muslim mosques from vandalism through stiffer penalties for people committing such a crime. It has also restricted the establishment of ...